Congestion Control in Wireless sensor networks Using TOPSIS and Percolate Congestion Control Algorithm (PCCA) - S.Prabhu , Dr.C.Chandrasekar (International Journal of Advanced Science and Technology, 2020)
Congestion control is a critical region inside wireless sensor networks (WSN), where traffic gets more prominent than the totaled or individual limit of the fundamental channels. Along these lines, unique contemplations are needed to develop more complex methods to dodge, distinguish, and resolve congestion. The obliged assets of the WSN should be thought of while concocting such methods to accomplish the greatest throughput. Different methodologies have been presented in the previous few years that incorporate steering protocols helped with congestion detection and control instrument, and committed congestion control protocols. In this paper we proposed TOPSIS and Percolate Congestion Control Algorithm (PCCA) for Congestion Control in Wireless sensor networks.